Sexual dimorphism in the level of special coordination ability of swimmers of the Sports Championships Schools - Stelmach, P.; Rydzik, L.; Ambrozy, T. (Journal of Human Sport & Exercise, 2022)
Background. Gender differences in the area of motor coordination skills have been the subject of many studies. Differences among school-age children are very often examined. However, reports describing the level of dimorphism in groups characterized by an almost identical lifestyle are less numerous. Objective. Examining the sexual dimorphism in the level of special coordination ability of swimmers of the Sports Championships Schools (SCS). Material & methods. The study was based on tests assessing the coordination motor skills of swimmers (CMS) in the same age group (14-16 years) and at a similar level of sporting performance. Tests were carried out under the same conditions and during the same preparation periods. Results. Based on the conducted research among swimming youth, both boys and girls, the obtained test results in tests measuring the level of special coordination skills clearly indicate a higher level of training these abilities among boys. The smallest differences between the examined groups occurred in the test of balance during rotation. Conclusion. The suppositions of the players' advantage in the trials requiring precision were confirmed. Also, the results showing a stronger dimorphism with a predominance of boys in the energy component are not surprising.